Unusual food plants from Oakbank Crannog, Loch Tay, Scottish Highlands : cloudberry, opium poppy and spelt wheat - Miller, Jennifer J.
Oakbank is one of 18 crannogs in Loch Tay, and the first in Britain to have been excavated underwater. The abundant and well-preserved plant remains indicate a prosperous society with a well-founded arable and pastoral agriculture. Opium poppy and spelt wheat remains imply trade and suggest high status. Cloudberry pips highlight long-range gathering, possibly during transhumance.